Sustainability of Organic Farming System of Lowland Paddy in Deli Serdang Regency, North Sumatra Province - Panjaitan, Ernitha; Indradewa, Didik; Martono, Edhi; Sartohadi, Junun (Proceeding International Conference on Global Resource Conservation, 2015)
The objectives of this study was to assess the farming system of organic lowland paddy to soil pollution compared with conventional farming system in Deli Serdang Regency. An environmental assesment in this research as limited to the soil pollution caused by pesticides and chemical fertilizers. Soil samples were grouped into low and upper layers. Each soil composites was collected from ten sampling points. Which each consist of 5 sampling points of organic paddy farming system and 5 sampling points of conventional paddy farming Â system. The results showed that the levels of pesticides and nitrate in paddy soil was influenced by soil layers, meanwhile although was not statistically significant, the levels of pesticides and nitrate increased due to the way of cultivation.The results indicated that in general the soil pollution on organic paddy farming system was lower than conventional farming. Levels of pesticides and nitrate in the soil layer 20-40 cm was higher than levels of pesticides in the 0-20 cm. Pesticides and nitrate leached by water gets into the deeper layers of soil. The increased level of pesticides in soil of conventional farming was higher 0.96 ppm during the dry season and lowest 0.38 ppm in the rainy season compared with organic farming. The increased level of nitrate in soil of conventional farming was higher 0.45 ppm during the rainy season compared with organic farming, however in the dry season, the level of nitrate in conventional farming was lowest 2.32 ppm compared with organic farming.Keywords: conventional farming; organic farming; paddy; sustainability